ENSURING THE SPECIFIED LEVEL OF COMBAT SURVIVAL OF ARMORED WHEELED VEHICLES AT THE ACCOUNT OF INCREASING THE RELIABILITY OF CHECKING THE TECHNICAL CONDITION OF THE ENGINES - Iohov, Oleksandr; Bielai, Serhii; Horielyshev, Stanislav (Honor and Law, 2022)
Controlling the technical condition of armored wheeled vehicles using existing means in conditions of constant fire resistance is not possible, as it requires decommissioning the equipment for a fairly long period of time. Therefore, the problem of ensuring the control of the technical condition of armored wheeled vehicles without decommissioning it with a reduction in the time cycle of monitoring its technical condition becomes especially urgent. Considering the fact that the vast majority of armored wheeled vehicles of the National Guard of Ukraine have a significant consumption of resources, the urgent task is to develop a more reliable method of monitoring the technical condition of the engines of armored wheeled vehicles for the timely elimination of possible malfunctions. The results of the analysis made it possible to propose a method aimed at achieving the necessary reliability of monitoring the technical condition of the engines of armored wheeled vehicles by means of spectral analysis of random signals that arise in the presence of malfunctions or violations of the algorithm of the functioning systems. The purpose of the article is to increase the reliability of monitoring the technical condition of the engines of armored wheeled vehicles by means of spectral analysis of random signals that arise in the presence of malfunctions or violations of the algorithm of operation of healthy systems. The proposed method of spectral analysis of the vibration signal of the diagnostic control of the technical condition of the engines of armored wheeled vehicles makes it possible to reduce time spent on simple transport, which improves the coefficient of operational readiness and the survivability of armored vehicles as a whole. The results of the analysis of the use of dynamic filters of the second order for spectral correlation analysis of random signals in comparison with narrow-band filters of small orders showed that the reliability of monitoring the technical condition of the engines of armored wheeled vehicles increases from 10 % to 20 %. Further research will be continued in the direction of adaptation of dynamic filters of the second order of spectral correlation analysis of random signals to control the technical condition of various engines of armored wheeled vehicles of the National Guard of Ukraine in various conditions of use.